Penafsiran Surat Al-Baqarah (2): 241 Terhadap Izin Perkawinan dan Perceraian Bagi Pegawai Negeri Sipil - Makinudin, Makinudin (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2015)
Indonesia sets a legal obligation of the ex-government employee husband, who had divorced his wife, in article 8, Peraturan Pemerintah No. 10 year 1983, so that the ex-husband does not facilitate divorce, especially the legal obligation to give up some of his salary for a living of the ex-wife until she gets marriage. This will certainly have a positive impact, especially for the ex-wife who has children and need lot of cost for their schooling. If the husband does not care about the fate of the children who regularly follow their mother, they will of course be displaced. Al-Qur'an, chapter al-Baqarah: 241 has a close relationship to article 8, Peraturan Pemerintah No. 10 year 1983, namely: (1) the obligation of the ex-government employee husband to give cost for the ex-wife's and the children's living; (2) the reason of the acceptable and valid benefit (maslahah). This benefit is classified as a secondary benefit (hajiyyah) namely keeping the soul, heredity, and honor, as intended to eliminate the difficulties and objections that are borne by the former wife of the ex-government employee husband. [Indonesia menetapkan kewajiban hukum dari mantan suami (PNS) yang telah menceraikan istrinya, yaitu dalam pasal 8, Peraturan Pemerintah Nomor 10 tahun 1983, bahwa mantan suami tidak mempermudah perceraian, terutama kewajiban hukum untuk memberikan beberapa dari gajinya untuk hidup mantan istri sampai dia menikah lagi. Hal ini tentu akan berdampak positif, terutama untuk mantan istri yang memiliki anak-anak dan perlu banyak biaya untuk sekolah mereka. Jika suami tidak peduli tentang nasib anak-anak yang menurut aturan mengikuti ibu mereka, mereka tentu saja akan mengungsi. Al-Qur'an, surat al-Baqarah: 241 memiliki hubungan dekat dengan pasal 8, Peraturan Pemerintah Nomor 10 tahun 1983, yaitu: (1) kewajiban suami karyawan ex-pemerintah untuk memberikan biaya untuk mantan istrinya dan hidup anak-anak; (2) alasan manfaat diterima dan valid (maslahah). Manfaat ini diklasifikasikan sebagai manfaat sekunder (hajiyyah) yaitu menjaga jiwa, keturunan, dan kehormatan, sebagaimana dimaksud untuk menghilangkan kesulitan dan keberatan yang ditanggung oleh mantan istri dari suami (PNS).]